A review of important electroencephalogram features for the assessment of brain maturation in premature infants. (September 2017) - Pavlidis, Elena; Lloyd, Rhodri O.; Mathieson, Sean; Boylan, Geraldine B.
Abstract: This review describes the maturational features of the baseline electroencephalogram (EEG) in the neurologically healthy preterm infant. Features such as continuity, sleep state, synchrony and transient waveforms are described, even from extremely preterm infants and includes abundant illustrated examples. The physiological significance of these EEG features and their relationship to neurodevelopment are highlighted where known. This review also demonstrates the importance of multichannel conventional EEG monitoring for preterm infants as many of the features described are not apparent if limited channel EEG monitors are used.Conclusion: This review aims to provide healthcare professionals in the neonatal intensive care unit with guidance on the more common normal maturational features seen in the EEG of preterm infants. Abstract :